Enhanced induction heating and self-healing performance of recycled asphalt mixtures by incorporating steel slag. (15th September 2022) - Yang, Chao; Wu, Shaopeng; Xie, Jun; Amirkhanian, Serji; Liu, Quantao; Zhang, Jinquan; Xiao, Yongli; Zhao, Zenggang; Xu, Haiqin; Li, Na; Wang, Fusong; Zhang, Lei
Abstract: Recycling reclaimed asphalt pavement (RAP) has attracted extensive attention for its environmental sustainability. As a typical industrial solid waste, steel slag with magnetic phase can facilitate the induction healing efficiency of asphalt mixtures. However, few researches focused on the healing characteristics of recycled asphalt mixtures with steel slag. Hence, this issue deserves systematic investigation. In this study, the chemical composition and static magnetic properties of steel slag with different particle size were estimated. And the induction heating performance, healing efficiency, multiple healing characteristic and healing rate after aging of their recycled asphalt mixtures were determined. The results indicate that magnetic hysteresis loops of steel slags reveal the typical narrow S-type curves, representing their magnetically soft characteristic with low coercivity. The highest Fe content and superior static magnetic properties are discovered in ASSF with particle sizes of 9.5–16 mm, and its saturation magnetization and coercivity gain up to 2.13 emu/g and 148.09 Oe. The ascending particle size of steel slag incorporated in recycled asphalt mixtures accelerates its induced temperature increment, effective heating depth and healing efficiency in contrast to the RAP addition. R7 with all component steel slag possesses the highest fracture energy of 685 J/m 2 and HRE of 51.6% after healing. Healing rate of recycled asphalt mixtures grows in the previous four cycles and then start to reduce during the fifth cycle. R40 demonstrates the maximum HRS of 57.9% after the fourth cycle with a 10.7% diminution than R0, which maintains a desirable level. Long term aging boosts the attenuation degree of the self-healing performance for RAM with the increase of RAP dosage. HRAS of R40 undergone aging declines by 21.3% and merely reaches 29.1% due to the faster aging rate and inferior diffusion velocity into the cracks of recycled asphalt in recycled asphalt mixtures.